2017
DOI: 10.17140/hroj-4-139
|View full text |Cite
|
Sign up to set email alerts
|

Double-Low Dose Protocol of Computed Tomography Pulmonary Angiography (CTPA) in the Diagnosis of Pulmonary Embolism: A Feasible Approach for Reduction of Both Contrast Medium and Radiation Doses

Abstract: CitationAldosari S, Al Moudi M, Sun Z. Doublelow dose protocol of computed tomography pulmonary angiography (CTPA) in the diagnosis of pulmonary embolism: A feasible approach for reduction of both contrast medium and radiation doses. ABSTRACTThis article discusses a hot topic on double low-dose protocol of computed tomography pulmonary angiography (CTPA) in the diagnosis of pulmonary embolism, with a special focus on a recent paper published in the British Journal of Radiology about the feasibility of this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…20 As an added benefit, low kV technique can improve coronary arteries' enhancement via increasing photoelectric events in low energy photons and their higher attenuation by contrast media. 17,[21][22][23][24] Therefore, low kV scanning allows reduction in contrast medium concentration, because of iodine k-edge absorption. 20,[25][26][27][28][29] This parallels with minimized risk of CIN, mainly in diabetic patients who consume metformin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 As an added benefit, low kV technique can improve coronary arteries' enhancement via increasing photoelectric events in low energy photons and their higher attenuation by contrast media. 17,[21][22][23][24] Therefore, low kV scanning allows reduction in contrast medium concentration, because of iodine k-edge absorption. 20,[25][26][27][28][29] This parallels with minimized risk of CIN, mainly in diabetic patients who consume metformin.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that lowering kV based on body mass index would be a practical approach to decrease patient dose without sacrificing the image quality . As an added benefit, low kV technique can improve coronary arteries’ enhancement via increasing photoelectric events in low energy photons and their higher attenuation by contrast media . Therefore, low kV scanning allows reduction in contrast medium concentration, because of iodine k‐edge absorption .…”
Section: Introductionmentioning
confidence: 99%